Photonic crystal resonators as bio-liquid sensing platforms in the terahertz band - Hanham,S; Watts,C; Ahmad,M; Otter,W; Lucyszyn,S; Klein,N (2019)
We describethe development of high quality(Q)factor photonic crystal resonators(PCRs)integrated with microfluidic systems to formthe basis ofhighly sensitive liquid sensing platformsforthe terahertz band.The strong confinement of the terahertz fieldincombinationwith the high Q-factor provided bythe PCR allows the measurement of thedielectric properties of sub-nanoliter liquid volumes. We demonstrate the utility of thisapproach by measuring the complex permittivity of several bio-liquids at 100 GHz.